2015
DOI: 10.1177/0194599815570880
|View full text |Cite
|
Sign up to set email alerts
|

Developing Effective Automated Feedback in Temporal Bone Surgery Simulation

Abstract: Objective We aim to test the effectiveness, accuracy, and usefulness of an automated feedback system in facilitating skill acquisition in virtual reality surgery. Study Design We evaluate the performance of the feedback system through a randomized controlled trial of 24 students allocated to feedback and nonfeedback groups. Setting The feedback system was based on the Melbourne University temporal bone surgery simulator. The study was conducted at the simulation laboratory of the Royal Victorian Eye and Ear Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…This may be due to the heterogeneity of the participant groups, difficulty of the simulation task, lack of prior exposure by participants and limited corrective instruction provided during or between attempts. Increased number of attempts in the simulation may be necessary before baseline performance expectations or gains in skill can be quantified 2,10 . No differentiation could be made between educational modality (video versus live demonstration), which may be attributed to inadequate exposures to the instructional materials and limitations of the educational environment.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the heterogeneity of the participant groups, difficulty of the simulation task, lack of prior exposure by participants and limited corrective instruction provided during or between attempts. Increased number of attempts in the simulation may be necessary before baseline performance expectations or gains in skill can be quantified 2,10 . No differentiation could be made between educational modality (video versus live demonstration), which may be attributed to inadequate exposures to the instructional materials and limitations of the educational environment.…”
Section: Discussionmentioning
confidence: 99%
“…15,19,20,23,24,25 The VR systems employed in these studies include the Stanford, OSU, University of Melbourne, Visible Ear, and VOXEL-MAN simulators.…”
Section: Methodsmentioning
confidence: 99%
“…A previous evaluation of the feedback system with stagebased random forest classifiers [12] showed that timely feedback was provided 88.6% of the time, and out of these feedback messages, 84.2% were accurate. This evaluation was based on the automated feedback provided to participants during the study.…”
Section: Validationmentioning
confidence: 99%
“…Wijewickrema et al [11] used these models to develop a feedback system that provides real-time advice on various aspects of surgical drilling technique. The system was shown to provide accurate and effective feedback [12].…”
Section: Introductionmentioning
confidence: 99%